Ensayo fotográfico : empoderamiento de los adultos mayores en las plazas del Centro Histórico de Quito - Pichuasamin Carvajal, Byron Xavier (2018)
This investigation make an theorist-photographic approach about the empowerment and participation that older adults performs as social and political subjects, through various social and symbolic practices that allow them to generate territorialities in a public space of the following squares of the Historic Center of Quito, (HCQ); San Francisco Independence Square, Theater Square and Santo Domingo. A photographic essay explores the tensions of meaning and power in the public space, that come from the various mechanisms of inclusion-exclusion that are exercised on this social group, problematizing those “behaviors of civility” socially accepted and those behaviors which are considered to be detrimental to the policies of Aesthetisation - Patrimonialization; from there, it is inquired about the following categories of analysis: Economic activities (older adults who exercise informal work or underemployment, outside of the municipal ordinances that prohibit this activities in the HCQ); Religious Cultural Manifestations (addresses the various practices around the creed in these squares) and The Allowed – The Forbidden register those practices about sociality and recreation in contrast to the condemned practices such as sex work, street people situation, etc.) From this analysis and registration, the study concludes that there are several ways in which the public space is designed to live or not; as well as; reveals various mechanisms of discrimination as the privatization of public space and gentrification.